Inflation Dynamics in Algeria - Samer Mehibel; Yacine Belarbi (Journal of Economics and Behavioral Studies, 2018)
In thispaper, we analyze Inflation Dynamics in Algeria between 2002 and 2016. We use a Vector Auto Regressive model (VAR), impulse response functions (IRF) and variance error decomposition (VDC) to uncover possible links between public spending component sand inflation. Wetest for the sources and dynamics of inflation in Algeria by focusing on public spending, since they are expected to exert a strong influence on the aggregate demand and hence inflation. According to the results we found, inflation in Algeria is persistent; shocks are lasting longer and having impact on the future inflation path. Social transfers and equipment spending are found to be the most contributing components of public spending in explaining inflation in Algeria.